'A spectacle for the cameras': the survival of a Lakeland leisure tradition, 1930- c.1955. Issue 2 (3rd May 2020) - Andrew, Rebecca
ABSTRACT: This article examines the survival of rushbearing, a rural leisure tradition in the English Lake District. As a region popular with tourists throughout the twentieth century, this case study offers important insights into how their presence shaped this 'traditional' leisure activity. Not only did annual rushbearing ceremonies offer opportunities for the region's sense of place to be presented to outsiders, they were also an important way for local communities to reaffirm their connection to the Lake District and its past. These occasions were, however, increasingly influenced by an awareness of external influences and outside judgements, as the region's popularity as a tourist destination boomed from the inter-war years. Although youth culture was increasingly standardised at a national level during this period, at a local level, young countrymen and women played an integral role in rushbearing's survival, which promoted an idealised version of 'traditional' country life. This annual community event is therefore a useful example through which to examine the interplay between rural leisure traditions, tourism, and the role of young people in the countryside during this period.